Factors Predicting Antibiotic use Behavior Among Healthcare Volunteers in Pathumthani Province, Thailand - อ่วมเกิด พัชร์สณธิ์; กรรมบุตร จีราภรณ์; ทองใบ วนลดา (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this research is to study the factors that predict the antibiotic use behavior of healthcare volunteers. The research applied the 3rd step, PRECEDE- PROCEED model. The population was healthcare volunteers in Pathumthani province, Thailand. The cluster and simple random sampling were used to recruit 205 people. The data were collected using interviews from January, 2018 to March, 2018. The research instrument was an interview questionnaire, consisting of the predisposing factors, enabling factors, reinforcing factors, and antibiotic use behaviors. Those were Cronbach’s Alpha coefficients in healthcare volunteer’s antibiotic use behavior data questionnaires at 0.86, in attitude of antibiotic use data questionnaire at 0.78, antibiotic use knowledge data questionnaire were KR21 coefficients at 0.86. The data were analyzed using descriptive statistics and multiple regression analysis method. The results revealed that antibiotic use behavior of volunteer was at a high range (M = 29.20, SD. = 2.38). The factors of attitude (ß = -0.264), with monthly income higher than 30,000 THB per month (ß = 0.163), being female (ß = -0.165), having antibiotic use knowledge and medicinal properties (ß = -0.134) in combination with significantly predicted the antibiotic use behavior of the healthcare volunteers in Pathumtani Province, Thailand at a significant level of .05, explaining 18 percent of the variance (F = 4.109, p<0.044) According to the above mentioned findings, the public health organizations should provide activities to promote the right understanding, knowledge of proper antibiotic use for healthcare volunteers that should build higher awareness and rationales for using antibiotics. In addition, they could be able to convey this knowledge to their community afterward.